Biogenic metal nanoparticles: A new approach to detect life on mars? - Simões, Marta Filipa; Ottoni, Cristiane Angélica [UNESP]; Antunes, André (My University, 2020)
Metal nanoparticles (MNPs) have been extensively studied. They can be produced via different methods (physical, chemical, or biogenic), but biogenic synthesis has become more relevant, mainly for being referred by many as eco-friendly and more advantageous than others. Biogenic MNPs have been largely used in a wide variety of applications, from industry, to agriculture, to health sectors, among others. Even though they are increasingly researched and used, there is still space for exploring further applications and increasing their functionality and our understanding of their synthesis process. Here, we provide an overview of MNPs and biogenic MNPs, and we analyze the potential application of their formation process to astrobiology and the detection of life on Mars and other worlds. According to current knowledge, we suggest that they can be used as potential biosignatures in extra-terrestrial samples. We present the advantages and disadvantages of this approach, suggest further research, and propose its potential use for the search for life in future space exploration.
Keywords: Astrobiology; Biogenic synthesis; Biosignatures; Life detection; Metal nanoparticles